PROTECTIVE ROLE OF GINSENG AGAINST GENTAMICIN INDUCED CHANGES IN KIDNEY OF ALBINO MICE - Qadir, Muhammad Irfan; Tahir, Mohammad; Lone, Khalid P; Munir, Bushra; Sami, Waqas (Journal of Ayub Medical College Abbottabad, 2011)
Background: Use of gentamicin is now limited due to its toxic effects, mainly on kidney and vestibular system. Herbal products including ginseng has been reported to possess protective effects against drugs induced nephrotoxicity in experimental animals. The current investigation was designed to evaluate the effects of ginseng on gentamicin induced nephrotoxicity. Methods: Eighteen male albino mice of 6-8 weeks age, were divided into 3 groups. Group-A served as control and was given normal mouse diet; Group-B was given 80 mg/Kg/day of gentamicin intraperitoneally dissolved in 1 ml of distilled water for fifteen days. Group-C was given 80 mg/Kg/day of gentamicin intraperitoneally dissolved in 1 ml of distilled water along with 100 mg/Kg/day of ginseng orally dissolved in 1 ml of distilled water, also for fifteen days. At the end of the experiment, blood was drawn from each animal by cardiac puncture for renal function tests. Each animal was then sacrificed and kidneys removed for routine histological studies. Results: In group B, weight of the animals and kidneys decreased and there was significant increase in mean serum urea, creatinine and intraluminal diameter (p<0.001) of proximal convoluted tubules as compared to the controls (groupA). Moderate to severe necrotic and degenerative changes in proximal convoluted tubules were seen in this group. When the Ginseng and gentamicin were given together (group-C), a statistically significant improvement in the mean body and kidney weight along with improvement in renal function tests and tubular diameter were seen (p<0.001). Conclusion: It appears that Ginseng has some protective role against gentamicin induced nephrotoxicity. Keywords: Gentamicin, ginseng, nephroprotective role, nephrotoxicity, serum urea, serum creatinine